Seven-year change of prevalence, clinical risk factors, and mortality of patients with carbapenem-resistant Klebsiella pneumoniae bloodstream infection in a Chinese teaching hospital: a case-case-control study - Kong, Haifang; Liu, Yong; Yang, Ling; Chen, Qianqian; Li, Yanchun; Hu, Zhidong; Feng, Xuequan; Chai, Yamin; Dong, Zuoliang (Frontiers in Microbiology, 2025)
Carbapenem-resistant Klebsiella pneumoniae bloodstream infection (CRKP-BSI) is a major public health threat worldwide. CRKP-BSI is associated with poor outcomes, elevated morbidity and mortality, and high healthcare costs. Therefore, the identification of risk factors for CRKP-BSI and mortality are critical for preventing and controlling CRKP in hospitals. This retrospective case-case-control study was conducted at General Hospital of Tianjin Medical University, a tertiary teaching hospital, from 2017 to 2023. It included 105 patients with CRKP-BSI (case group 1) and matched 105 patients with carbapenem-susceptible K. pneumoniae bloodstream infection (CSKP-BSI) (case group 2). The control group was selected at a ratio of 1:1:1 (case group 1: case group 2: control) from patients with a positive blood culture (except for K. pneumoniae infection) to analyze risk factors associated with the two case groups and compare the 30-day survival curves using multivariable logistic regression and Kaplan-Meier analyses. Multivariate analysis revealed that liver disease was a risk factor for K. pneumoniae-BSI, and exposure to carbapenem [odds ratio (OR) = 3.24], tigecycline (OR = 3.43), and glucocorticoids (OR = 4.64) were independent risk factors for CRKP-BSI. The 30-day mortality of the CRKP-BSI group was 30.5%, and patient groups, respiratory diseases (HR = 3.52), use of 3rd-generation cephalosporins (HR = 1.92), mechanical ventilation (HR = 2.14), and central venous catheter insertion (HR = 2.85) were independent risk factors, whereas a shorter length of hospitalization was a protective factor for 30-day mortality. The in-hospital mortality in the CRKP-BSI group was 55.2%, and arterial catheter use (OR = 3.76) was an independent risk factor for in-hospital mortality. Several factors were identified to contribute to the development of CRKP-BSI. CRKP isolates were resistant to most antibiotics. Reducing CRKP-BSI-related mortality requires comprehensive consideration of underlying diseases, judicious antibiotic use, and invasive procedures. The high morbidity, mortality, along with the limited therapeutic options for CRKP-BSI, underscore the need for improved detection, identification of risk factors to develop effective preventive measures, and development of novel agents with reliable clinical efficacy against CRKP.